The oncogenic role of NOTCH1 as biomarker in oral squamous cell carcinoma and oral lichen planus - Ensieh Sagheb Sadeghi; Fatemeh Saeid Nematpour; Nooshin Mohtasham; Farnaz Mohajertehran (Wolters Kluwer Medknow Publications, 2023)
Background: Oral squamous cell carcinoma (OSCC) is the most common type of oral cancer with heterogeneous molecular pathogenesis. Oral lichen planus (OLP) is demonstrated potentially can transfer to OSCC malignant lesions. Unfortunately, there are no definitive prognostic and predictive biomarkers for the clinical management of OSCC patients. The present research is the first study that compared an oral premalignant lesion such as OLP to malignant lesions like OSCC for NOTCH1 expression levels to better understand its oncogenic or tumor suppressive role. Materials and Methods: In this cross-sectional study, mRNA expression of NOTCH1 was evaluated by quantitative polymerase chain reaction in 65 tissue-embedded Paraffin-Block samples, including 32 OSCC and 33 OLP. Furthermore, we collected demographic information and pathological data, including tumor stage and grade. The association between NOTCH1 and GAPDH gene expressions was determined by Chi-squared, Spearman, and Mann-Whitney tests. A P < 0.05 was considered statistically significant for all statistical analyses. Results: Comparison of OSCC and OLP groups showed a statistically significant difference between the quantitative expression of the NOTCH1 gene (P < 0.001). Qualitative gene expression was divided into low expression and high expression. Both study groups demonstrated a statistically significant gene expression difference (P < 0.001). There was a statistically significant difference between age and NOTCH1 expression in the OLP group (P = 0.036). There was no correlation between NOTCH1 expression and age, gender, tumor grade, and stage. Conclusion: Since the OSCC is a malignant lesion and the OLP showed the possible nature of malignancy transformation, we can consider the NOTCH1 as a biomarker for the assessment of the tumorigenesis process with a definition of a standard threshold for potentially malignant lesions and malignant OSCC tumors.